Effects of Leucaena condensed tannins of differing molecular weights on in vitro CH 4 production - Huang, X.D.; Liang, J.B.; Tan, H.Y.; Yahya, R.; Ho, Y.W. (2011)
Condensed tannins (CT) exhibit nutritional, environmental and veterinary benefits in ruminant production. It is known that effects of CT on animal nutrition is multi-factorial, but their molecular weight (MW) and/or chemical structures play a key role in their biological activity. The average MW of five CT fractions obtained from Leucaena hybrid-Bahru (LLB) was determined using mass quadrupole time-of-flight liquid chromatography/mass spectrometry. CT within each fraction had varying degrees of polymerization with up to hexamers and molecular weights of 1348.80Da identified in the first fraction, and 494.56Da in the fifth fraction. Results show that CT fractions with the highest MW had in the highest inhibition of CH 4 production, being 62 lower than the control. In addition, the amount of CH 4 as a proportion of total gas also decreased with CT compared to control, suggesting a direct effect of CT on CH 4 production with those of higher MW exhibiting anti-methanogenic activity.